It’s a jungle out there: challenges in postgraduate research writing - Joanna Joseph Jeyaraj, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Literature in English for academic purposes and postgraduate education suggests that research writing is challenging for students and acts as a barrier to timely completion. In Malaysia, postgraduate numbers are steadily increasing, yet high attrition rates remain a significant problem. Research into thesis writing appears to be an area that is slowly beginning to grow among Malaysian scholars, however most studies focus on public higher education institutions in the country. This study seeks to provide a voice for students from an off-campus university in Malaysia by investigating their writing experiences. The aim was to explore research writing challenges because there seemed to be a lack of any formalised structure which supported the writing process in this institution. Semi-structured interviews were carried out with six full-time postgraduate research students from non-native Englishspeaking backgrounds and data were analysed using a general inductive approach. It was found that academic language demands were challenging, and this affected writing and disciplinary socialisation. Additionally, some students felt there was an absence of clear direction in writing. Finally, isolation was experienced and resulted in a need to reach out to other communities. These findings reveal the diverse needs of students; if addressed, more timely completion rates and greater student learning experiences may be achieved.